Reduce or redirect? Which social marketing interventions could influence demand for traditional medicines? - Moorhouse, TP; Coals, PGR; D'Cruze, NC; Macdonald, DW (Elsevier, 2020)
The global trade in wildlife is a threat to species conservation and animal welfare. A key driver is demand for traditional medicines (TMs). We present an initial experimental survey of demand reduction and demand redirection interventions aimed at changing the behaviour of TM consumers in China and Vietnam. Treatment respondents (n = 1600) were shown TM products, with messages outlining their conservation, welfare or human health impacts, and asked their intention to buy these products in the future. Control respondents (n = 400) were shown nothing. All respondents were then shown a ‘herbal’ (plant-based) substitute, and asked how likely they would be to buy it. Respondents were finally shown a list of TMs and asked to select those they would buy.